Design of a Web-Based Employee Attendance Application for PT Cakraindo Mitra Internasional with QR Code - Gusnandar Silaen, Fery; Kurniawan, Fahmi (Cattleya Darmaya Fortuna, 2025)
The online attendance management system at PT. Cakraindo Mitra Internasional is developed to enhance the effectiveness of recording attendance and submitting overtime. The platform employs QR codes for real-time and precise attendance tracking. Featuring a responsive design and data export capabilities, this solution aids both managers and staff in overseeing daily attendance and handling overtime efficiently and practically.